MEDIA IKLAN YANG RAMAH WISATAWAN MILENIAL - hakim, imam nur (Jurnal Kepariwisataan Indonesia : Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Millennials grow massively. Their immense purchasing power also supports it. So, many sectors in the world make it a market opportunity. This leap is also done by the tourism sector, especially in Indonesia. The generation referred to as the-next-future-tourist has different characteristics in travelling compared to the previous generation. As a result, there are differences in the choice of promotional media that are friendly to millennial tourists. DMO needs to take a different approach and can no longer use conventional media choices to promote. Through a descriptive qualitative approach, this study will use a literature study pattern to link millennial tourist preferences with the right choice of media in the promotion. This study found that social media, influencer's role, email marketing, website, review site, and search engines became ?friendly? media to promote to millennial tourists. Key words: Promotional Media, Tourism Advertising, Millennial Tourist